THE EFFECT OF QUALITY WORK LIFE, EMPLOYEE BURNOUT, AND WORKLOAD ON WORK-LIFE BALANCE OF WORK FROM HOME EMPLOYEES IN SURABAYA - Taufik Deswanto Mochtar; Nanis Susanti (International Journal Labs, 2022)
Since the Covid-19 pandemic hit diverse international locations withinside the global, the coverage of operating from domestic or work at home (WFH) has come to be the selection of many parties, such as in Indonesia. Working from domestic can also additionally revel in a few obstacles, inclusive of our consciousness could be divided among homework and lots of workplace paintings that has piled up. This stability is likewise encouraged through numerous different elements, such as high-satisfactory of labor lifestyles, worker burnout, and workload. This have a look at objectives to show and examine the impact of the variables of high-satisfactory paintings lifestyles, worker burnout, and workload at the paintings-lifestyles stability of personnel operating from domestic. The approach used is a quantitative approach and explanatory studies as form of studies. The populace used purposive sampling, particularly Surabaya City personnel who're currently/have accomplished work at home with a pattern of a hundred people. Data evaluation makes use of SmartPLS three to degree the outer model, internal model, and speculation testing. The effects confirmed (1) Quality Work Life had a extensive impact on Work-Life Balance, (2) Employee Burnout had a extensive impact on Work-Life Balance, and (3) Workload had a extensive impact on Work-Life Balance.